2006
DOI: 10.1128/jvi.01013-06
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Biochemical Analysis of Purified Human Immunodeficiency Virus Type 1 Produced from Infected Monocyte-Derived Macrophages

Abstract: Human immunodeficiency virus type 1 (HIV-1) infects CD4؉ T lymphocytes and monocytes/macrophages, incorporating host proteins in the process of assembly and budding. Analysis of the host cell proteins incorporated into virions can provide insights into viral biology. We characterized proteins in highly purified HIV-1 virions produced from human monocyte-derived macrophages (MDM), within which virus buds predominantly into intracytoplasmic vesicles, in contrast to the plasmalemmal budding of HIV-1 typically see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
474
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(498 citation statements)
references
References 78 publications
23
474
0
1
Order By: Relevance
“…ANXA2 is a multifunctional protein and is involved in many cellular processes, such as fibrinolysis, exocytosis, endocytosis, cell-cell adhesion, and cell motility (36,37,48). ANXA2 has been linked to the life cycle of other positive-sense single-stranded RNA viruses, such as hepatitis C virus (49)(50)(51) and HIV (52)(53)(54). In both cases, a viral protein has been reported to interact with ANXA2 in infected cells, and silencing of ANXA2 affected the infectivity of the viruses.…”
Section: Discussionmentioning
confidence: 99%
“…ANXA2 is a multifunctional protein and is involved in many cellular processes, such as fibrinolysis, exocytosis, endocytosis, cell-cell adhesion, and cell motility (36,37,48). ANXA2 has been linked to the life cycle of other positive-sense single-stranded RNA viruses, such as hepatitis C virus (49)(50)(51) and HIV (52)(53)(54). In both cases, a viral protein has been reported to interact with ANXA2 in infected cells, and silencing of ANXA2 affected the infectivity of the viruses.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain how viruses like HIV can cross the blood-brain barrier. HIV and exosome feature a similar size and share some protein content [82]; and HIV virions are partly Page 13 of 32 A c c e p t e d M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 13 generated into the MVB [82]. In addition recent developments demonstrated that HIV enters the endocytic track of target cells for infection [83].…”
Section: Exosome Internalizationmentioning
confidence: 99%
“…When infected, dendritic cells, monocytes, macrophages and lymphocytes can produce both exosomes and HIV virions [82] with similar density, which require separation by immunocapture or appropriate gradient density separation. Also exosomes compete with HIV for the virus entry in endocytic compartment [83].…”
Section: 2spreading Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Annexin A1 (AnxA1) is one of the most famous family members and there is a wealth of information on its protective anti-inflammatory and proresolving effects (Perretti and D'Acquisto, 2009 (Kattenhorn et al, 2004;Dry et al, 2008;Loret et al, 2008;Vidick et al, 2013), human immunodeficiency virus type 1 (HIV-1) (Chertova et al, 2006), vesicular stomatitis virus (VSV) (Moerdyk-Schauwecker et al, 2009, Rift Valley fever virus (Nuss et al, 2014) and IAV (Shaw et al, 2008), and recent evidence points to a function of the AnxA1 receptor FPR2 in IAV replication (Tcherniuk et al, 2016). AnxA2 is a component of herpesviruses (Wright et al, 1994(Wright et al, , 1995Varnum et al, 2004;Zhu et al, 2005;Dry et al, 2008;Loret et al, 2008;Gershom et al, 2012;Vidick et al, 2013), IAV (LeBouder et al, 2008;Shaw et al, 2008;Liu et al, 2012), HIV-1 (Chertova et al, 2006), human papilloma virus (HPV) type 16 (Woodham et al, 2012), hepatitis C virus (HCV) type 1 (Backes et al, 2010), VSV (Moerdyk-Schauwecker et al, 2009, vaccinia virus (Chung et al, 2006), Rift Valley fever virus (Nuss et al, 2014) and Newcastle disease virus (Ren et al, 2012). AnxA5 is associated with herpes simplex virus (HSV) type 1 (Loret et al, 2008), HIV-1 (Chertova et al, 2006), VSV (Moerdyk-Schauwecker et al, 2009, Rift Valley fever virus (Nuss et al, 2014), and IAV (Shaw et al, 2008).…”
Section: Annexins As Host Cell Derived Virulence Factorsmentioning
confidence: 99%